RISK-BASED LICENSING AS LICENSING REFORM IN INDONESIA BASED ON GOVERNMENT REGULATION NUMBER 5 THE YEAR 2021 - Hillary Abigail Praise; Adrian E. Rompis; R. Adi Nurzaman (Jurnal Poros Hukum Padjadjaran, 2022)
The purpose of this paper is that the author tries to explain the birth of the concept of risk-based licensing (RBA) in Indonesia which is regulated in Government Regulation Number 5 of 2021. The author elaborates on the transformation of the concept of risk-based approach license and its role in replacing the previous licensing concept. The author also analyzes this policy more deeply through the ROCCIPI Method to find weaknesses and provide recommendations. Licensing in Indonesia so far still has many weaknesses, including regulations that are not yet harmonious, the difficulty of licensing bureaucracy, and low investment realization. With this, the government carried out deregulation and debureaucratization to give birth to licensing reform in Indonesia. The government introduced a new licensing concept called the Risk-Based Approach or RBA which changed the licensed-based concept to risk-based. Based on the scope of research, in writing this manuscript, the author uses a normative juridical research method. The conclusion that comes from this paper is that the RBA is a bold step taken by the government, and so far it has had a good impact in terms of accelerating the issuance of permits. On the other hand, there are still many components that need to be maximally improved by the government such as the readiness of the OSS RBA system, readiness of human resources, and also improving the quality of public services so that licensing reform in Indonesia is not just an idea but can be fully realized through this regulation.